Тенденція розвитку методів рендерингуWeb-сайтів для пошукової оптимізації сайтів (SEO) - Брухтій, С. С. (ХНУРЕ, 2024)
This article encompasses advanced approaches and challenges in employing contemporary rendering methods for SEO. It examines modern rendering techniques such as SSR, CSR, ISR and Rehydration, which are pertinent and can be utilized for SEO purposes. The significance of rendering methods for successful SEO performance is covered.
Keywords: рендеринг; rendering; веб-сайт; SEO